Comparison of food extraction techniques and impact of nitrogen fertilization on the potential allergenicity of soybean related to birch pollen-food allergy syndrome - Verscheure, Paulien; Daelemans, Robin; Coorevits, Lieve; Van Gerven, Laura; Aerts, Raf; Schrijvers, Rik (Frontiers in Allergy, 2025)
BackgroundBirch pollen-food allergy syndrome is triggered by cross-reactive allergens in plant-based foods. Environmental factors such as nitrogen fertilization may influence food allergenicity, but this has not been studied before.MethodsWe compared and optimized protein extraction protocols for birch-homologue foods, including apple, carrot, and soybean. Various extraction buffers and mixing methods were tested for consistency and protein yield. We applied this to a pilot study assessing potential changes in the allergenic potential of plant-based foods due to altered nitrogen availability. A greenhouse experiment was conducted in which soybean plants were subjected to different nitrogen fertilization treatments. Allergenicity was evaluated using ex vivo basophil activation testing in five individuals with birch pollen-food allergy syndrome.ResultsNo major differences were observed between the tested extraction protocols, and key allergens were detectable in all food sources. In the pilot experiment, fertilized soybeans showed visible changes in size, a smaller shape, a different protein profile, and lower basophil reactivity compared to unfertilized soybeans.ConclusionOur findings support the feasibility of standardized extraction methods. Varying nitrogen fertilization in soybeans resulted in altered physical, proteomic, and allergenic characteristics in this pilot study. Our results highlight the need for further research on environmental influences on food allergy.